Sex-Related Differences in Heart Failure After ST-Segment Elevation Myocardial Infarction - Cenko, Edina; van der Schaar, Mihaela; Yoon, Jinsung; Manfrini, Olivia; Vasiljevic, Zorana; Vavlukis, Marija; Kedev Sasko; Miličić, Davor; Badimon, Lina; Bugiardini, Raffaele (Elsevier BV, 2019)
ST-segment elevation myocardial infarction (STEMI) complicated by symptoms of acute de novo heart failure is associated with excess mortality. Whether development of heart failure and its outcomes differ by sex is unknown.